2010
DOI: 10.1148/radiol.10091367
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted Imaging Improves the Diagnostic Accuracy of Conventional 3.0-T Breast MR Imaging

Abstract: Purpose:To evaluate the incremental value of diffusion-weighted (DW) imaging and apparent diffusion coeffi cient (ADC) mapping in relation to conventional breast magnetic resonance (MR) imaging in the characterization of benign versus malignant breast lesions at 3.0 T. Materials and Methods:This retrospective HIPAA-compliant study was approved by the institutional review board, with the requirement for informed patient consent waived. Of 550 consecutive patients who underwent bilateral breast MR imaging over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
225
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(247 citation statements)
references
References 28 publications
17
225
0
3
Order By: Relevance
“…entiation of benign and malignant breast lesions and may increase the accuracy of conventional breast MRI assessment (17,19). Ei Khouli et al (17) showed that ADC values significantly improved the ability of DCE-MRI to discriminate between benign and malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…entiation of benign and malignant breast lesions and may increase the accuracy of conventional breast MRI assessment (17,19). Ei Khouli et al (17) showed that ADC values significantly improved the ability of DCE-MRI to discriminate between benign and malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Ei Khouli et al (17) showed that ADC values significantly improved the ability of DCE-MRI to discriminate between benign and malignant lesions. Yabuuchi et al (21,22) concluded that the application of DWI together with DCE-MRI contributes to an improved diagnostic accuracy of breast MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normalization is thought to overcome factors that affect ADC values, including ADC variations across the menstrual cycle (as reported previously by Partridge et al [49]) and variations of scanning parameters. The normalized ADC value with a cut-off point of 0.7 significantly improved the diagnostic performance of DWI in discriminating benign from malignant lesions (48).…”
Section: Breast Applicationsmentioning
confidence: 97%
“…Another attempt to improve the diagnostic performance of diffusion-weighted MRI in breast MRI was embodied in the suggestion of El Khouli et al (48) to normalize the ADC value of breast lesions to the ADC value of the ipsilateral remote glandular tissue (Fig. 3).…”
Section: Breast Applicationsmentioning
confidence: 99%